Growth of Socio-Entrepreneurship Role of Universities in Economic and Legal Space of Russia: Issues of Theory and Practice - BARKOV, Aleksey V.; GRISHINA, Yana S.; LESKOVA, Yulia G.; SEROVA, Olga A. (Journal of Advanced Research in Law and Economics; Vol 9 No 3(33) (2018): JARLE, Volume IX, Issue 3(33), Summer 2018DO - 10.14505/jarle.v9.3(33).10, 2018)
Topicality of the studied problem is caused by the goal of formation of the legal model for participation of Universities in innovational entrepreneurship and growth of their socio-entrepreneurship role in economic and legal space of Russia. The purpose of the research consists in determining the peculiarities of the legal status of University in Russia, which combines three missions: educational, research, and entrepreneurial, which are related to social entrepreneurship. The scientific methods used in this research include analysis, synthesis, comparison, generalization, rather-legal method, and method of literal and systemic interpretation of the norms of law. Results: the study presents the authors’ offers for successful realization of the project ‘Universities as centers for space of innovations’, conducted in Russia, which includes the conclusions on change of the civil and legal status of Universities and minimization of commercialization in their activities. The materials of the paper have practical value for specialists in the sphere of economic and law and persons who conduct scientific research in the sphere of legal regulation of Universities’ activities, as well as persons involved in legislative activities.